Amazon: A story of accumulation through intellectual rentiership and predation. (July 2022) - Rikap, Cecilia
This article elaborates on intellectual monopoly theory as a form of predation and rentiership using Amazon as a case study. By analysing Amazon's financial statements, scientific publications and patents, we show that Amazon's economic power heavily relies on its systematic innovations and capacity to centralize and analyse customized data that orients its business and innovations. We demonstrate how Amazon's innovation activities have evolved over time with growing importance of technologies related to data and machine learning. We also map Amazon's innovation networks with academic institutions and companies. We show how Amazon appropriates intellectual rents from these networks and from technological cooperation with other intellectual monopolies. We argue that Amazon, as other data-driven monopolies, predates value from suppliers and third-party companies participating in its platform. One striking characteristic of Amazon is the low rate of reported profits. The centrality of innovations leads us to suggest an alternative calculation that shows that Amazon's profits are not as low as they appear in Annual Reports. We also argue that lower profits are coherent with Amazon's rentiership and predatory strategy since they contribute to the avoidance of accusations of excessive market power. Finally, the paper offers preliminary observations on: (i) the complementarities between financial and intellectual rentierism and (ii) how data-driven intellectual monopoly expands big corporations' political power. Going beyond the specific case of Amazon, we thus contribute to a better understanding of the role of lead firms and power dynamics within innovation networks.